The relationship between self-efficacy in reading with language proficiency and reading comprehension among ESL learner's - Habibian, Maryam; Roslan, Samsilah (International Institute for Science, Technology & Education, 2014)
This work investigates the relationship between self-efficacy in reading with language proficiency and reading comprehension. The sample utilized is comprised of 64 postgraduate students from two universities, namely Universiti Putra Malaysia and Universiti Malaya. The students are selected from several Master and PhD programs of faculty of Education, Engineering, and Agriculture. The instruments employed to collect the data, was the Scale of Belief Self-Efficacy Comprehension, and reading comprehension test. Quantitative analysis is utilized to analyze the gathered data. The result indicates that, there is a significant correlation between reader self-efficacy and reading comprehension. Moreover, readers’ self-efficacy in different levels of foreign language proficiency is different, and readers who possess high level of proficiency, perform reading task better than readers who are considered as high self-officious. In addition, the result demonstrates that, self-efficacy and language proficiency are the key factors in academic achievement. Furthermore, students who are self-efficacious can perform the task better than who are not, and students who possess high level of language proficiency are more successful in the process of reading.